The investigation of antifungal susceptibilities of Kluyveromyces marxianus and Clavispora lusitaniae strains isolated from various clinical specimens - Atalay, Altay; Koç, Ayşe Nedret; Çakır, Nuri; Mutlu Sarıguzel, Fatma; Sağıroğlu, Pınar (Journal of Surgery and Medicine, 2021)
Background/Aim: C. albicans remains the most common pathogen responsible for invasive candidiasis. On the other hand, increased rates of candidiasis have been reported worldwide, caused by other Candida species (such as K. marxianus and C. lusitaniae). Considering these uncommon yeasts may be crucial pathogens in the future, it is preferable to describe the in-vitro activities of antifungal agents as potential options for their treatments. This study aimed to evaluate the in-vitro activity of nine different antifungal agents that are routinely used to contribute to the treatment of the infections caused by K. marxianus and C. lusitaniae. Methods: The study included 21 K. marxianus and eight C.lusitaniae strains isolated from various clinical specimens of patients with suspected invasive fungal infection. Conventional identification was confirmed using the molecular methodology of DNA sequencing analysis. Antifungal susceptibilities of the isolates were tested using the Sensititer Yeast One Test Panel Y06 kit, a colorimetric microdilution test. Results: For K. marxianus, amphotericin B had the highest geometric mean MIC (1 μg/mL) and voriconazole had the lowest geometric mean MIC (0.010 μg/mL). For C. lusitaniae, flucytosine had the highest geometric mean MIC (8 μg/mL) and voriconazole had the lowest geometric mean MIC (0.011 μg/mL). Conclusion: Considering that these two species, rare causes of invasive candidiasis nowadays, may become important pathogens in the future, it is reasonable to investigate the in-vitro activities of antifungal agents that can be used in their treatment.